1980
DOI: 10.1159/000241264
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucocorticosteroid Hormones on the Levels of Rat Liver Carbamoylphosphate Synthase (Ammonia) and Arginase Activity during Ontogenesis

Abstract: In rats, hepatic carbamoylphosphate synthase (ammonia) and arginase activities are closely related during development. Activities increase sharply during the last 4 prenatal and first 4 postnatal days and during the 3rd postnatal week. Decreases are observed between 4 and 9 days after birth, and after weaning, during adolescence. During senescence activities increase again. Before birth, treatment with prednisolone is far less effective in increasing enzyme activities than during the first 2 postnatal weeks, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 5 publications
1
25
1
Order By: Relevance
“…Note the different scales on they axis. the decrease in liver wet weight after natural birth is due to the loss of glycogen and protein (29)(30)(31)(32)45). Therefore, the 25% decrease in cell volume in glucose-supplemented fetuses, relative to the fetuses taken directly after caesarian section, occurs also after natural birth.…”
Section: Effects Of Short-term Starvationmentioning
confidence: 99%
“…Note the different scales on they axis. the decrease in liver wet weight after natural birth is due to the loss of glycogen and protein (29)(30)(31)(32)45). Therefore, the 25% decrease in cell volume in glucose-supplemented fetuses, relative to the fetuses taken directly after caesarian section, occurs also after natural birth.…”
Section: Effects Of Short-term Starvationmentioning
confidence: 99%
“…1). A similar increase in the accumulation of enzyme is also found in vivo in the prenatal period and was explained by a recruitment of previously inactive hepatocytes for enzyme synthesis [27]. Immunocytochemical staining of fetal liver sections has since supported this explanation [28].…”
Section: Discussionmentioning
confidence: 56%
“…The preparation of the tissue, the enzyme assays, the protein and the deoxyribonucleic acid estimates were as described previously (40). All values referred to in the graphs and text were obtained from at least two litters and 2 -4 preparations per litter, and depicted or expressed as means ± SD.…”
Section: Hormonesmentioning
confidence: 99%
“…In a previous paper (40) it was shown that daily administration of synthetic glucocor ticosteroid hormones resulted in only a faint stimulation of carbamoylphosphate synthase and arginase activities in the prenatal period compared to the postnatal period (see also : 16).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation